Performance evaluation of a nearest level control-based TCHB multilevel inverter for PMSM motors in electric vehicle systems - Mohd Said, Nurul Ain; Hossain, Md Showkot; Abd Halim, Wahidah; Jidin, Auzani; Hasan, Md Akib; Wan Abdul Munim, Wan Noraishah (Elsevier B.V., 2025)
Transistor Clamped H-Bridge (TCHB) multilevel inverter (MLI) is receiving considerable research interest because it can provide excellent outputs with a reduced number of switches and DC voltage sources compared to traditional MLI topologies. This study investigates the application of a nearest level control (NLC) technique in a three-phase TCHB inverter fed permanent magnet synchronous motor (PMSM) with a focus on improving power quality and minimizing total harmonic distortion (THD). The proposed system is modeled in MATLAB/Simulink, incorporating a field-oriented control (FOC) strategy with a proportional-integral (PI) controller for precise speed regulation of the PMSM. The NLC technique is selected for its ability to reduce switching losses and improve inverter efficiency. Key performance metrics, including THD, efficiency, and dynamic response, are analyzed under various operating conditions. Results indicate that the NLC technique reduces THD to 4.73 %, achieving smoother output waveforms and enhanced power quality. Additionally, the system demonstrates over 97 % efficiency, reliable dynamic performance, and accurate reference speed tracking during real-life driving cycle testing. These findings highlight the potential of the NLC-based TCHB inverter as a robust solution for high-performance motor drives in electric vehicle (EV) applications.